Predictors of Sleep Duration and Sleep Disturbance in Children of a Culturally Diverse Region in North-Eastern Greece - Nena, Evangelia; Cassimos, Dimitrios; Kaditis, Athanasios; Kourantzi, Maria; Trakada, Georgia; Economou, Nikolaos-Tiberio; Nikolaidis, Pantelis T.; Rosemann, Thomas; Knechtle, Beat; Steiropoulos, Paschalis; Tsalkidis, Angelos (Frontiers in Pediatrics, 2020)
BACKGROUND-AIM: Aim of this study was to examine sleep characteristics of children and explore associations with various socio-demographic factors, in an area of Greece characterized by cultural diversity. METHODS: A questionnaire about children’s sleep habits had been distributed to parents of children who visited the pediatric outpatient clinic of University General Hospital of Alexandroupolis, for a medical examination and health certificate, for participation to sports activities. Children with chronic health conditions were excluded. RESULTS: In the study, 449 children (27.1% belonging to minorities) were included, aged 7.6±2.9 years. Most of them (81.7%) slept after 10 pm, with mean nocturnal sleep duration 9.4±1.2 hours. The most commonly reported disturbance was snoring (26.2%). Age and high educational level of the mother were both important determinants for sleeping late [OR 1.139 (1.033-1.255); p=0.009 and OR 1.086 (1.004-1.175); p=0.040, respectively. The latter was also associated with absence of any reported sleep disorder in children [OR 0.934 (0.877-0.994); p=0.031]. A longer sleep duration was reported among Roma children (p=0.022), which was more overt in girls (mean sleep duration 10.4±1.6 hours). In the Roma group also, prevalence of sleep disorders was higher. CONCLUSION: Age progression and maternal educational level along with cultural background seem to be related with variations in sleep characteristics of children, in a culturally diverse population of Greece.